2016
DOI: 10.1155/2016/4327081
|View full text |Cite
|
Sign up to set email alerts
|

Association between Self-Reported Bruxism and Sleeping Patterns among Dental Students in Saudi Arabia: A Cross-Sectional Study

Abstract: Objectives. The aim of this cross-sectional study was to identify sleeping patterns among dental students and their association with self-reported bruxism in Riyadh Colleges of Dentistry and Pharmacy (RCsDP). Methods. A cross-sectional study was performed including 549 students (67 men and 482 women). A structured questionnaire was adopted from The PSQI (The Pittsburgh Sleep Questionnaire Index) used for data collection. It included questions which are categorized into sleeping habits, sleep-related symptoms, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 37 publications
0
24
0
2
Order By: Relevance
“…2 However, some authors suggested that a bruxism diagnosis relying on this method should be considered as "possible" bruxism and the definite diagnosis can only be made on the basis of selfreport in conjunction with clinical examination and polysomnographic (PSG) recordings. 1 To date, international studies on university students have often investigated the prevalence of bruxism only in certain disciplines of education 6,7 or among all university students without selecting a specific population. 8,9 The overall prevalence of clenching teeth and grinding teeth was reported at 46.8% and 19.8% respectively in young adults in Turkey in an investigation conducted via telephone interviews.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2 However, some authors suggested that a bruxism diagnosis relying on this method should be considered as "possible" bruxism and the definite diagnosis can only be made on the basis of selfreport in conjunction with clinical examination and polysomnographic (PSG) recordings. 1 To date, international studies on university students have often investigated the prevalence of bruxism only in certain disciplines of education 6,7 or among all university students without selecting a specific population. 8,9 The overall prevalence of clenching teeth and grinding teeth was reported at 46.8% and 19.8% respectively in young adults in Turkey in an investigation conducted via telephone interviews.…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of SB has been particularly investigated in the field of dental medicine. 7,23 Dental practice may be associated with stress factors 6 and a very high SB prevalence was reported in Saudi Arabia at 31.1%. 7 Bruxism prevalence of 33.9% was found in a study conducted with students from a dental faculty in Konya, Turkey.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Second, in the current study we relied on single, self-report items to assess dental irritation. Although a considerable number of studies also used a method of single items to estimate bruxism (e.g., Ahlberg et al, 2003 ; Shokry et al, 2016 ), this may pose a threat to the validity and the reliability of the measure. Moreover, assessing sleep bruxism via self-report measures can yield inaccurate results; on the one hand, Bader and Lavigne (2000) stated that people are often not aware of having sleep bruxism and thus it may lead to an underestimation of the prevalence; yet, on the other hand, Maluly et al (2013) found that self-reports may overestimate the diagnosis of sleep bruxism, despite the existing overlap between the objective and the subjective measures.…”
Section: Discussionmentioning
confidence: 99%
“…The two items were significantly correlated [ r = 0.63 (0.51, 0.72), p < 0.001], however, we used them separately in order to explore correlations when individuals are unaware of their grinding (represented by item #2). Single self-report items have been used to assess sleep bruxism in additional studies ( Ohayon et al, 2001 ; Winocur et al, 2011 ; Shokry et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%